Physical restraints: An ethical dilemma in mental health services in China - Junrong Ye; Aixiang Xiao; Lin Yu; Hongmei Wei; Chen Wang; Tianyun Luo (Elsevier, 2018)
Given that physical restraints cause adverse effects to patients and nurses, their wide and frequent use has resulted in various clinical and ethical controversies in mental health services. The rate of physical restraints is significantly higher in China than in other countries. Some western and domestic media blamed relevant institutions for compromising the basic rights of psychiatric patients. Therefore, this study aims to collect and synthesize the relevant ethical evidence and to provide corresponding guidance for the nursing practice based on the current situation of the mainland of China. This study synthesized the ethical issue according to the ethical principle of autonomy, justice, beneficence, and non-maleficence. Given the current situation where the nursing workforce is limited and the mental health service is under-developed in China, applying physical restraints in the psychiatric inpatients to guarantee the safety of patients and nurses is crucial. In regard to respect the basic rights of psychiatric patients, it is recommended to protect the their autonomy, and eliminate the adverse effects of physical restraint. This goal would be achieved by ensuring the informed consent, providing humane care, and regulating the implementation of physical restraints. Keywords: Ethics, Mental health, Nursing care, Physical restraint